Evaluation and psychometric status of the brief resilience scale in a sample of Malaysian international students - Amat, Salleh; Mhd Subhan; Wan Jaafar, Wan Marzuki; Mahmud, Zuria; Ku Johari, Ku Suhaila (Canadian Center of Science and Education, 2014)
The purpose of this study is to examine the psychometric status of the Brief Resilience Scale (BRS). The BRS is a brief self-rating questionnaire to measure resilience. This instrument consists of six items and was administered on 120 international students studying at a public university in Malaysia. The sample consists of 76 male and 44 female, with a mean age of 24.4 years old. The BRS met the requirement for the implementation of PCA based on the Bartlett test of Sphericity and the Kaiser Mayer Olkin. Factor analysis reveals a single factor with eigenvalues above 1.0, which accounted for 73.54% of the total variance. Reliability analysis using Cronbach’s Alpha was .93, indicating that the scale has good reliability. This study demonstrates that BRS is appropriate to be used by college personnel and counselors to examine and identify resiliency among college students in Malaysia. Suggestions for future study are also discussed.